A sustainable euro area with exit options - Ritzen, Jo; Haas, Jasmina (Bonn, 2017)
"All explorations of the future of the Euro show serious risks for its survival in the present form. The road map of the Five EU Presidents presented in 2015 is far from sufficient to reduce the risks of the Euro zone falling apart by Brexit type developments or new economic shocks. The EU Presidents rely too much on high international economic growth smoothing the convergence in labor productivity between EU member states, while the more likely low growth scenario shows a serious risk of the Euro?area falling apart in a chaotic way, through further divergence in labor productivity, through new Banking crises or through the popular vote in response to fiscal and labor market reform. The Presidents argue for strengthening the Banking union with an independent watchdog, with a single resolution mechanism for Bank defaults and for a European credit deposit insurance system. The support for these proposals is overwhelming. They also argue for more transfer of sovereignty on financial policy and for debt mutualisation (sharing of the risks of country debt among all EU countries). This is unlikely to happen, while at the same time the urgency for dealing with the drag imposed by the high debt levels of many EU countries on economic growth is high. We propose that the EU negotiates a New Deal between the highly indebted Euro countries and the other Euro countries. In this deal the trust is built that the richer countries agree on debt mutualization against the assurance of an automatic exit from the Euro area at non?compliance with the agreed (and simplified) rules."